Students' perceptions about the use of wiki. analysis of an experience of collaborative learning at the University of Girona - Albert Ruda González (Ediciones Universidad de Salamanca, 2013)
<!--[if gte mso 9]> 0 0 1 47 260 USAL 2 1 306 14.0 <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false ES JA X-NONE <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" P